Прагматизм і плюралізм як рушії розвитку великого міста - Рубл, Б. (Народна творчість та етнологія, 2012)
Blair A. Ruble. Pragmatic and Pluralism as the Movers of Urban Development. The author describes a century history of the American city Chicago beginning from arriving of the first foreigners in the XVIIIth century till it turned into one of the most modern and developed cities in the USA at the beginning of the XXIst century. The author gives a dynamic picture of the establishment of the metropolis with its industry, architecture, and cultural heritage.